Dimension in the Noble Qur’an: An Analytical Study - Khalil, Mohamed; Abdullah, Muhammad (Islamic Sciences Journal, 2023)
Talking about distance and proximity in the Noble Qur’an is one of the serious issues that necessitate understanding its meanings, as it carries within it the greatness of retribute and the danger of punishment. The study is divided into an introduction, two sections and a conclusion. The introduction highlights the definition of dimension and where it is mentioned in the Holly Quraa’n. Section one defines the dimension linguistically and idiomatically. Section two elaborates on the distance in the Holy Qur’an, its causes by which one obtains prestige and proximity. The conclusion sums up the most important findings of the study. The importance of the study springs from emphasizing the stories of past nations who disobeyed Allah Almighty and thus distanted themselves from Allah’s mercy.